SANKSI ADAT TERHADAP PERKAWINAN EXOGAMI DI DESA PAKRAMAN TENGANAN PENGRINGSINGAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM, PROVINSI BALI - I Putu Sudarma; Pande Kadek Dharmajayanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Indigenous Village Community of Tenganan Pegrisingan, Tenganan Village, Manggis District, Karangasem Regency, Bali Province is classified as a Balinese-Aga community which is still thick with customary prohibitions on exogami marriage. Violations of the marriage ban are subject to customary sanctions. Customary sanctions are not only imposed on the bride and groom, but also the bride’s parents in the village. Sanctions in exogamous marriages in Pakraman Village, Tenganan Pegringsingan are subject to reason, namely preservation of traditions, kinship system, and maintaining health. The form of customary sanctions in exogamy marriage is in the form of fines and moral sanctions, while the implication is to show inconsistency in marriage, and lose all of their rights as village manners in Pakraman Tenganan Pegringsingan Village.